Quantification of a subsea CO2 release with lab-on-chip sensors measuring benthic gradients. (September 2021) - Schaap, Allison; Koopmans, Dirk; Holtappels, Moritz; Dewar, Marius; Arundell, Martin; Papadimitriou, Stathys; Hanz, Rudolf; Monk, Samuel; Mowlem, Matthew; Loucaides, Socratis
Highlights: A subsea release of CO2 was detected and quantified with a novel approach. Autonomous lab-on-chip sensors on a lander measured pH and total alkalinity. The pH signals showed decreases in pH of >0.6 and strong vertical gradients. pH and hydrodynamic measurements enabled an estimate of CO2 emission rate. This technique could be adapted to a wide range of in situ benthic gradient studies. Abstract: We present a novel approach to detecting and quantifying a subsea release of CO2 from within North Sea sediments, which mimicked a leak from a subsea CO2 reservoir. Autonomous lab-on-chip sensors performed in situ measurements of pH at two heights above the seafloor. During the 11 day experiment the rate of CO2 release was gradually increased. Whenever the currents carried the CO2 -enriched water towards the sensors, the sensors measured a decrease in pH, with a strong vertical gradient within a metre of the seafloor. At the highest release rate, a decrease of over 0.6 pH units was observed 17 cm above the seafloor compared to background measurements. The sensor data was combined with hydrodynamic measurements to quantify the amount of CO2 escaping the sediments using an advective mass transport model. On average, we directly detected 43 ± 8% of the released CO2 in the water column. Accounting for the incomplete carbonate equilibration process increases this estimate to up to 61 ± 10%. This technique can provide long-term in situ monitoring of offshore CO2 reservoirs and hence provides a tool to support climate change mitigation activities. It could also be applied to characterising plumes and quantifying other natural or anthropogenic fluxes of dissolved solutes.